Capitalism and Economic Stability: Direct Versus Monetary and Fiscal Controls: Discussion - Tongue, William W. (Journal of Finance, 1950)
WILLIAM W. TONGUE*: One of the striking things about these papers on direct vs. monetary and fiscal controls is the apparent unanimity of opinion among professional economists that direct controls are undesirable and should be used only as a last resort. Mr. Hagen has done an admirable job of summarizing the case against direct controls from the theoretical point of view. Mr. Turner has stressed the practical problems to be faced, especially the necessity for a large measure of public support, and has compiled an exhaustive and scholarly review of the various controls actually used in the postwar period. From this I think we can agree that direct controls should be used only under very special circumstances, such as in wartime when a rapid shift of resources is required; in specific situations where political factors are dominant, as in the case of export controls; and possibly in some areas of the economy where the price system does not work as flexibly as it might, e.g., steel allocations for defense and Mr. Turner's freight car example. Thus, I find myself in fairly general agreement with both Mr. Hagen and Mr. Turner. Any differences I might have are rather trivial, with one possible exception. The exception relates to Mr. Turner's appraisal of the postwar controls which are now dead, but for which Mr. Turner seems to have a fond recollectionl. I detect a willingness on his part to allow vague notions of equity to color his conclusions without examining the alternative of what might have been accomplished in a freer market. But these are rather small differences in comparison with the wide area of agreement that indirect controls should be relied upon in peacetime to keep the economy on a reasonably even keel. This raises the question of how far indirect controls fiscalmonetary controls, as Mr. Hagen has put it can go in performing this function. Mr. McCracken has mentioned some of the difficulties confronting fiscal policy. No one disagrees that the weapon is powerful enough to be effective if it actually can be used. Most of the problems in using it revolve around the question of timing, especially the problem of getting Congress and the public to act in time and in the right direction. But we are dealing with monetary as well as fiscal policy. And the monetary weapon has not received the attention it deserves, in